Does Governance Impact on the Foreign Direct Investment-Growth Nexus in Sub-Saharan Africa? (2014)
The central question this paper sought to tackle was “does the quality of institutions matter for the relationship between Foreign Direct Investment (FDI) and economic growth?” Using macroeconomic data on 27 Sub Saharan African (SSA) economies and six distinct measures of governance the findings showed that control of corruption, political stability and government effectiveness matter for the influence of FDI on economic growth in SSA. This key finding was found to be robust even in models where these three governance indicators were interacted with FDI. Furthermore, the results from threshold-type sample splitting showed that in the sample containing countries with a higher level of governance, the positive impact of FDI on growth has larger magnitude vis-à-vis the comparator group with poorer governance indicators. This significant threshold effects remained robust across specifications